Influence of Cultivar, Anti‐Browning Solutions, Packaging Gasses, and Advanced Technology on Browning in Fresh‐Cut Apples During Storage. Issue 2 (24th May 2016) - Putnik, Predrag; Bursać Kovačević, Danijela; Herceg, Korina; Levaj, Branka
Abstract: Objectives were to compare differences in color change (Δ E ab ∗ ) over shelf‐life (SL) for 2 apple cultivars (Golden Delicious, GD; Cripps Pink, CP) subjected to 5 antibrowning treatments (ABT) (no treatment/control; ascorbic + citric acid with/without ultrasound; Ca‐ascorbate with/without ultrasound) in presence of normal or modified atmosphere (MA). Plus, to assess influences of respiration rates on Δ E ab ∗ for all combinations of cultivars and ABT. Original color of apples was better preserved in MA. The absence of ABT showed highest Δ E ab ∗, while all ABT showed similar change in color regardless of MA application. Browning prevention of ascorbic + citric acid may be improved with application of ultrasound. Production of CO2 oscillated with color change for both cultivars with different ABT. The GD will endure browning better than CP, while Ca‐ascorbate was one of the best antibrowning agents. All created mathematical models are freely available in computer simulation ("Anti‐browning Apple Calculator – C.A.P.P.A.B.L.E.©"; apple.pbf.hr or 31.147.204.87). Practical Applications: The main purpose of presented models was to integrally compare influence of modified atmosphere packaging in prevention of apple browning. Hence, models can be used to calculate optimal combination of industrial parameters and to compare calculated results against relevant economic managerial decisions. For example, models are useful to answer questions such as to what extent is the use of modified atmosphere or antibrowning treatment economically justified for the industrial fresh‐cut apple production. Hence, by optimizing relevant production parameters they can be used to extend the length of fresh‐cut apple shelf‐life and economic benefits while providing quality foods to consumers. Created computer simulation offers selection of various production settings and calculation of optimal values for particular fresh‐cut processes. Simulation settings include packaging size, volumetric concentration of gases, apple mass, packaging film, different permeances, and other.